Association between childhood dimensions of attention deficit hyperactivity disorder and adulthood clinical severity of bipolar disorders. (April 2017) - Etain, Bruno; Lajnef, M; Loftus, J; Henry, C; Raust, A; Gard, S; Kahn, JP; Leboyer, M; Scott, J; Bellivier, F
Background: Clinical features of attention deficit hyperactivity disorder can be frequently observed in cases with bipolar disorders and associated with greater severity of bipolar disorders. Although designed as a screening tool for attention deficit hyperactivity disorder, the Wender Utah Rating Scale could, given its factorial structure, be useful in investigating the early history of impulsive, inattentive or mood-related symptoms among patients with bipolar disorders. Methods: We rated the Wender Utah Rating Scale in 276 adult bipolar disorder cases and 228 healthy controls and tested its factorial structure and any associations with bipolar disorder phenomenology. Results: We confirmed a three-factor structure for the Wender Utah Rating Scale (' impulsivity/temper ', ' inattentiveness ' and ' mood/self-esteem '). Cases and controls differed significantly on Wender Utah Rating Scale total score and sub-scale scores ( p -values < 10 −5 ). About 23% of bipolar disorder cases versus 5% of controls were classified as ' WURS positive ' (odds ratio = 5.21 [2.73–9.95]). In bipolar disorders, higher Wender Utah Rating Scale score was associated with earlier age at onset, severity of suicidal behaviors and polysubstance misuse; multivariate analyses, controlling for age and gender, confirmed the associations with age at onset ( p = 0.001) and alcohol and substance misuse ( p = 0.001). Conclusion: Adults with bipolar disorders who reported higher levels of childhood symptoms on the Wender Utah Rating Scale presented a more severe expression of bipolar disorders in terms of age at onset and comorbidity. The Wender Utah Rating Scale could be employed to screen for attention deficit hyperactivity disorder but also for ' at-risk behaviors ' in adult bipolar disorder cases and possibly for prodromal signs of early onset in high-risk subjects.